Estimating the Normal and Reference Aortic Pulse Wave Velocity for the New Zealand Population: Improving Stroke and Cardiovascular Risk Prediction - Dahiya, Ekta Singh (Auckland University of Technology, 2020)
Arterial stiffness is expressed as the reduced capability of physiological expansion and contraction of arteries during changes in blood pressure (BP). It is measured as carotid-femoral pulse wave velocity (cf-PWV) and is well-established as an additional, independently predictive metric for cardiovascular disease (CVD) events, particularly in the presence of diabetes, obesity and stroke. Age and hypertension are the two risk factors that are consistently and independently associated with arterial stiffness. Current New Zealand (NZ) guidelines make no recommendations for measuring arterial stiffness during CVD risk assessment for any of the major ethnic groups. This is partly due to limited information about the normal and reference values of PWV in the NZ population. The present study is a first step towards building this evidence-base to enhance the accuracy of prediction of stroke and CVD risk in the healthy adult population in NZ. It is aimed at estimating normal and reference PWV values and investigating their association with established cardiovascular risk factors. This observational cross-sectional study included 120 participants grouped into three age groups (18-30, 31-60, and >60 years) and four BP categories (normal, elevated, stage 1 and stage 2). Participants were subjected to measurement of cf-PWV using Doppler ultrasound imaging for three to five cardiac cycles in a supine position. Descriptive and inferential analysis was made for the Normal Value Population (NVP) and Reference Value Population (RVP). Based on the positive correlation of cardiovascular risk factors to PWV, linear regression models for predicting PWV were developed. The mean PWV for the whole study population was 5.88 ± 1.49 m/s and increased systematically with age (p<0.001) with a more profound rise in the RVP group (p<0.001, z =-4.98). This overall mean PWV value is lower than that found in studies conducted overseas. However, mean PWV values among the age groups were not different between the NVP and RVP groups (p>0.05). Additionally, a significant difference in mean PWV in the European and non-European population (p= 0.004) indicated ethnicity being an important part of the assessment. The cf-PWV was found to be positively correlated with age (r=0.71), mean BP (r=0.49), BP categories (r=0.50), and being in the NVP or RVP group (r=0.46) (each having p<0.01). Our multiple linear regression model accounted for 57% of the variance in predicting PWV using variables- age, BMI, BP category and being in NVP or RVP group. Mean PWV in the 18-30 age group was unexpectedly lower at high BP levels when compared to all age groups in the normal BP group category. Mean PWV at ‘elevated BP’ levels were lower than for other BP categories. In conclusion, this study provides an initial dataset of normative PWV values in healthy New Zealanders. A positive correlation was found between PWV and being in the NVP or RVP group besides other cardiovascular risk factors, and this was a study demographic specific finding. The overall low PWV values in the NZ cohort compared with the regression equations reported from European, American, and African studies may be due to a unique ethnic mix of the study population and warrants further investigation. This study can serve as a starting point for future studies to refine the use of PWV for CVD risk prediction, with larger sample sizes and the inclusion of other cardiovascular risk predictors.
Keywords: Pulse wave velocity; Arterial stiffness; Normal and reference pulse wave velocity values; Cardiovascular risk factors; Bioimpedance